Dental radiography and safety awareness: Insights from radiographers, dentists, and students in a cross-sectional study - Moawia Gameraddin; Alaa Abdulkhalq Alessa; Hajar Sulaiman Aloufi; Shatha Dhaifallah Alzaidi; Awadia Gareeballah; Hassan Ibrahim Alsaedy; Kamal Alsultan; Mariam Khogaly Supair; Ahmed Ali Alharthi; Emadeldin Mohamed Mukhtar; Ali Abdelrazig; Magbool Alelyani (PLoS ONE, 2025)
Background Dental radiographs are crucial diagnostic tools for oral disorders, but their low-level radiation can pose health risks over time because of its cumulative effects. Objectives This study aimed to assess awareness and attitudes regarding dental radiography and safety among dentists, radiographers, dentistry students, and radiography students in western Saudi Arabia. Methods This cross-sectional survey study was conducted in the western region of Saudi Arabia. A total of 309 participants were included in the study. A questionnaire containing 13 multiple-choice questions was administered to dentists, radiographers, dentistry students, and radiography students. The Statistical Package for Social Sciences (SPSS 23) was used for data analysis. Results The mean knowledge and attitude scores of the participants were 61.09% and 65.13%, respectively. The mean score knowledge of dentists was 6.8 out of 12, that of radiographers was 7.04 out of 12, that of radiography students was 6.42 out of 12, and that of dentistry students was 6.83 out of 12. The attitude score was 35.45 out of 55, for dentists; 36.21 out of 55, for radiographers; 36.54 out of 55, for radiography students; and 34.79 out of 55, for dentistry students. The knowledge score increased significantly in participants who had Ph.D. and M.Sc. degrees (p value =  0.008). There was no significant variation in knowledge regarding gender, age, area of employment, or experience (p value < .05). The participants exhibited a positive attitude toward dental radiographic examination and radiation safety, with no significant difference observed among the groups (p value > .05). Conclusion This study indicates good awareness among dentists, radiographers, and students about dental radiography and safety, with higher education levels indicating greater awareness and a positive attitude. The safety and knowledge of dental radiography exposure vary among groups, highlighting the need for continuous education and standardized training to improve the understanding and usage of radiation hazards.